PENGARUH BAURAN PEMASARAN (LOKASI, HARGA, PROMOSI) TERHADAP KEPUASAN PELANGGAN DULANG RESORT AND RESTO BANDUNG - Mega Indah Edityawati; Fx Widari Eva Astuti (Jurnal Gici Jurnal Keuangan dan Bisnis, 2021)
The development of hotel business in Bandung is growing rapidly, so that the competition in the hospitality business is increasingly demanding that the company always strive to improve the quality of its products. One of the quality of services and marketing mix to meet customer expectations. This research was conducted to know the marketing mix location, price and promotion to customer satisfaction Dulang Resort & Resto Bandung. This research method is quantitative with the type of research used is survey research. The selection of the sample was done by purposive sampling. As for the sample totalled 75 respondents, using multiple linear regression analysis. Regression test results showed that 58,1% costumer satisfaction factors can be explained by the location, price and promotion while remaining 41,9% explained by other factors not examined in this study. F test results show that the simultaneous variable location, price and promotion effect significantly to costumer satisfaction. The t-test results show that the partially variable location and price influential positively and significantly to costumer satisfaction. While variable promotion doesn’t significantly influence of customer satisfaction.